Cartilage graft and temporal muscle fascia graft in revision myringoplasty: a comparison of anatomical and functional results with an innovative surgical technique - Canale, Andrea; Boldreghini, Marco; Abboud, Ili; Peluso, Patrizia; Vestrini, Elisa; Riva, Gluseppe; Albera, Andrea (Frontiers in Neurology, 2025)
BackgroundThe temporal muscle fascia is the most widely used type of tissue graft in revision myringoplasty procedures. The aim of this study was to verify if the use of a cartilage graft may be a valid alternative to temporalis fascia. Tympanic reperforations are frequent after myringoplasty, especially in complicated, large, or anterior perforations, so we decided to compare the neodrum stability of two different surgical techniques.Materials and methodsThe study was conducted on 42 patients who underwent revision myringoplasty, carried out with the overlay technique, between 2004 and 2020. In all patients, the retroauricular approach was used. The subjects included in the study were divided into 2 groups: the former was treated with a cartilage graft, while in the latter a temporalis fascia graft was used. In the comparison of the two groups, the following outcomes were taken into consideration: engraftment rate, incidence of complications, pre- and postoperative air conduction pure tone average and air-bone gap.ResultsThe success rate was 100% for the first group and 83.3% for the second, with a statistically not significant difference. Among the subjects treated with cartilage graft, complications were observed in 8.3% of the cases, while in patients treated with fascia graft the observed complication rate was 43.3% (p = 0.03), maybe due to the shorter follow-up period of the first group. The improvement of the air conduction pure tone average was greater with cartilage graft (p = 0.02), whereas the difference between air-bone gap closures in the two groups was not statistically significant.ConclusionThe cartilage graft can represent a valid alternative to temporal muscle fascia, guaranteeing excellent engraftment, fewer complication rate and satisfactory hearing outcomes.